PENGARUH STRATEGIC ORIENTATION, GOVERNMENT REGULATION TERHADAP GREEN SUPPLY CHAIN MANAGEMENT DAN ENVIRONMENTAL PERFORMANCE - Antin Rakhmawati; Kusdi Rahardjo; Andriani Kusumawati; Muhammad Nizar (AdBispreneur : Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, 2019)
This study examines and explains the relationship of income factor variables from the application of the green supply chain management concept, namely the strategic orientation and government regulation, and further effect on. The object of this research is small and medium enterprises which are associated with the traditional semi-modern greengrocery market in Malang Regency. This study uses census sample method by involving all the owners of traditional semi-modern greengrocery market. The results of this study indicate that, firstly, strategic orientation and government regulation have a significant positive impact on green supply chain management, secondly, green supply chain management has a significant positive effect on environmental performance, thirdly, strategic orientations and government regulation have a significant positive impact on environmental performance through green supply chain management.Penelitian ini menguji dan menjelaskan hubungan variabel yang menjadi faktor income dari penerapan konsep green supply chain management , yaitu strategic orientation dan government regulation, yang kemudian membentuk environmental performance. Objek penelitian ini adalah usaha kecil menengah yang terasosiasi pada pasar sayur tradisional-semi modern Kabupaten Malang. penelitian ini menggunakan metode sampel jenuh dengan melibatkan seluruh pemilik UKM pasar sayur tradisional- semi modern. Hasil penelitian ini menunjukkan bahwa; pertama strategic orientation berpengaruh positif signifikan terhadap green supply chain management, kedua goverment regulation berpengaruh positif signifikan terhadap green supply chain management, ketiga green supply chain management berpengaruh positif signifikan terhadap environmental performance, keempat strategic orientation berpengaruh positif signifikan terhadap environmental performance melalui green supply chain management, dan yang kelima government regulation berpengaruh positif signifikan terhadap environmental performance melalui green supply chain management.